Role of microRNAs in skin aging and its potential therapeutic interventions - Usman PP, Ashikha Shirin; Sekar, Durairaj; Tusubira, Deusdedit (Aging Pathobiology and Therapeutics, 2024)
The skin, the largest and most important organ of the body, serves diverse functions such as protection from the outside, temperature regulation, etc. It is composed of 3 layers: hypodermis, dermis, and epidermis. As the skin ages, it undergoes morphological and anatomical changes. Wrinkle formation and sagging are the main physical changes visible on the skin. Aging is caused by extrinsic and intrinsic factors that affect the morphology and function of the skin. Intrinsic aging is driven by biological and genetic factors, while extrinsic aging is influenced by environmental factors. Recent findings show the contribution of miRNAs in skin aging, particularly in replicative senescence. They regulate the expression of genes post-transcriptionally and control functions like collagen modulation, elastin synthesis, etc. This review explores the role of miRNAs in skin aging and details their role in cellular functions, including collagen synthesis. This review also describes the types and characteristics of skin aging, structural alteration in different layers of skin, and therapeutic interventions of miRNA in skin aging. Knowledge of miRNA involvement in aging will help to introduce new therapies in antiaging and skin care technology. The intricate relationship between environmental and genetic factors that cause skin aging is discussed, emphasizing the role that miRNAs play in this complex process. In addition, potential therapeutic interventions are described, highlighting the need for deeper knowledge of the molecular mechanisms of skin aging for effective, innovative future research.
Keywords: Skin aging; MiRNA; Collagen; Cellular senescence; Therapeutic interventions; Skin structure